Gaya Bahasa Asonansi dan Aliterasi pada Antologi Puisi Romances Sans Paroles - Icha Priliskha Yunisty; Nurul Hayana; Yuliarti Mutiarsih (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
This research aims to explain the analysis figure of speech of assonance et alliteration in poems anthology by Paul Verlaine. The research questions discussed in this research are how the assonance and the alliteration found in those poems by focusing on the repetition of vowels and consonants phonemes in an array. The method used in this research is descriptive-qualitative, by analyzing data contained in the poetry anthology Romances Sans Paroles in the form of sentences. The repetition of phonemes both assonance and alliteration was encountered 137 times. 61 assonances and 76 alliterations were found. The data is dominated by the phoneme [R] which is a type of vibrating shear consonant that found 11 times.